2015
DOI: 10.18088/ejbmr.1.4.2015.pp9-17
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective glance at automatic detection of epileptic spike in electroencephalogram

Abstract: Automatic detection of epileptic spikes is an important clinical application. It has been developed nearly 40 years. Yet the current automatic detection results are still not as reliable as experienced human interpreters, mainly due to the complex morphology of spikes and the similarity between paroxysmal events in brain activities. By reviewing the previous work, it is noticeable that the implementation of wavelet, ANN and spatiotemporal analysis show promising prospect.By reasonable combination of detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(161 reference statements)
0
1
0
Order By: Relevance
“…Epileptiform sharps are detected using a variety of algorithms such as deterministic finite automata (DFA) [ 3 ], geometrical features and artificial neural networks [ 4 ], cross-correlation [ 5 ], and dynamic time warping [ 6 ]. A recent review reported that these algorithms can detect epileptiform sharps with approximately 90% accuracy [ 7 ]. Algorithms for the automatic detection of SSWs have also been introduced in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Epileptiform sharps are detected using a variety of algorithms such as deterministic finite automata (DFA) [ 3 ], geometrical features and artificial neural networks [ 4 ], cross-correlation [ 5 ], and dynamic time warping [ 6 ]. A recent review reported that these algorithms can detect epileptiform sharps with approximately 90% accuracy [ 7 ]. Algorithms for the automatic detection of SSWs have also been introduced in the literature.…”
Section: Introductionmentioning
confidence: 99%